Análise Experimental da Turbulência em Escoamentos Rápidos - Elsa Carvalho (2013)
The present paper is devoted to the study of different characterizing variables of turbulence in supercritical flows. Among the different variables calculated one has the statistical moments: mean, standard deviation, skewness and flatness; the kinetic energy dissipation rate, etc. The measurements were carried with a LDA system. The LDA signal was processed in order to filter outliers and to allow the determination of the turbulent spectrum. Finally the obtained results for the turbulent variables are presented. These will be part of a data base with turbulence data in supercritical flows